Chocolate in Seventeenth-century England and Spain: An Edited Transcript of the Earl of Sandwich's Journal - Loveman, Kate (Food & History, 2022)
Abstract In the late 1660s, the first Earl of Sandwich and his aide John Werden compiled a remarkable set of information on the manufacture and consumption of chocolate in Spain and England. These details, entered into Sandwich’s diary, included an exceptionally valuable chocolate recipe supplied by Charles II himself. From Madrid, Werden provided illustrated accounts of chocolate manufacture in Spain and of elite ways to consume the drink. He supplied detailed guidance on making frozen delicacies, while Sandwich recorded perhaps the earliest workable recipe for a chocolate ice in English. They appear to have been gathering information not just for purposes of gourmandizing, but with an eye to the Royal Society’s investigations into the history of trades and to England’s colonial plans for Jamaica. Published here for the first time, with an introduction, translations and explanatory notes, Sandwich’s manuscript offers vivid insights into the technologies, customs and motives surrounding the adoption of chocolate from the Americas into Spanish and English cultures. Résumé Dans les années 1660, le premier comte de Sandwich et son assistant John Werden ont compilé un ensemble remarquable d’informations sur la fabrication et la consommation du chocolat en Espagne et en Angleterre. Les détails inscrits dans le journal de Sandwich comprenaient une recette particulièrement précieuse de chocolat fournie par Charles II lui-même. Depuis Madrid, Werden a envoyé à Sandwich des descriptions illustrées de la fabrication du chocolat en Espagne et de sa consommation en boisson par les élites. Il a inclus des conseils sur la fabrication de délices surgelés, tandis que Sandwich a consigné peut-être la première recette pratique d’une glace au chocolat en anglais. Ils semblent avoir collecté des informations non seulement à des fins de gourmandise, mais aussi dans l’intérêt des projets coloniaux de l’Angleterre en Jamaïque et des recherches de la Royal Society sur l’histoire des métiers. Publié ici pour la première fois, avec introduction, traductions et notes explicatives, le manuscrit de Sandwich offre un aperçu vivant des technologies, des coutumes, et des motivations entourant l’adoption du chocolat des Amériques dans les cultures espagnole et anglaise.